Pragmatics Lesson Analysis in the context of ESP course - Zulfiya Khabirova (Researchparks Publishing, 2023)
This article is devoted to an analysis of conducting the class in the context of ESP (English for Specific Purpose) to enhance awareness of pragmatic behavior in the requesting situation. The results in this article emphasize the value of pragmatics in ESP courses understanding and implementing pragmatic principles into a lesson. This article's ultimate goal is to close the gap between academic understanding and real-world application, encouraging a more thorough and contextually appropriate method of teaching language in ESP classes.